The impact of organizational training & development practices on the performance of employees - a perception from Transcom Beverages Limited - Hossain, Mehrab (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.